Reference and point-of-care testing for G6PD deficiency: Blood disorder interference, contrived specimens, and fingerstick equivalence and precision. - Sampa Pal (Public Library of Science (PLoS), 2021)
Certain clinical indications and treatments such as the use of rasburicase in cancer therapy and 8-aminoquinolines for Plasmodium vivax malaria treatment would benefit from a point-of-care test for glucose-6-phosphate dehydrogenase (G6PD) deficiency. Three studies were conducted to evaluate the performance of one such test: the STANDARD™ G6PD Test (SD BIOSENSOR, South Korea). First, biological interference on the test performance was evaluated in specimens with common blood disorders, including high white blood cell (WBC) counts. Second, the test precision on fingerstick specimens was evaluated against five individuals of each, deficient, intermediate, and normal G6PD activity status. Third, clinical performance of the test was evaluated at three point-of-care settings in the United States. The test performed equivalently to the reference assay in specimens with common blood disorders. High WBC count blood samples resulted in overestimation of G6PD activity in both the reference assay and the STANDARD G6PD Test. The STANDARD G6PD Test showed good precision on multiple fingerstick specimens from the same individual. The same G6PD threshold values (U/g Hb) were applied for a semiquantitative interpretation for fingerstick- and venous-derived results. The sensitivity/specificity values (95% confidence intervals) for the test for G6PD deficiency were 100 (92.3-100.0)/97 (95.2-98.2) and 100 (95.7-100.0)/97.4 (95.7-98.5) for venous and capillary specimens, respectively. The same values for females with intermediate (> 30% to ≤ 70%) G6PD activity were 94.1 (71.3-99.9)/88.2 (83.9-91.7) and 82.4 (56.6-96.2)/87.6(83.3-91.2) for venous and capillary specimens, respectively. The STANDARD G6PD Test enables point-of-care testing for G6PD deficiency.